COMENIUS E O DIREITO À EDUCAÇÃO: A VISÃO PIONEIRA A CAMINHO DA UNIVERSALIDADE - Cardoso, Karina Litardi Pereira (2014)
The hypothesis of the present thesis was Comenius and his thought compose one of the structural bases of the right to education, as it is currently understood. In order to discuss it, a dialogue between the thought of Comenius and the World Declaration on Education for All in Jomtien, 1990, UNESCO was sought. Jan Amos Comenius, educationalist and moravian bishop of the XVII century, endeavored in the creation and dissemination of his panshopic proposal in society, having the education as main part in the culture renovation. It was intended to present Comenius as a pioneer of education, considering his defense for an universal education within an unequal social context in mid sixteen hundreds, as well as the present, the recognition of his pioneering by the very UNESCO, considering him the Organizations spiritual antecessor. The educationalist aimed a knowledge systematization in panshopic key, represented by the triad omnes, omnia, omnino - teach everything in-depth to everyone. Therefore, the specifically objectives were : a) to know the phases of his life, covering his works, theological and pedagogical basis and experiences in his historical context; b) to present his educational thought; c) to comprehend specifically his panshopic proposal, that connects to the right to education. The methodological choice in the historical-documentary analysis, inspiration to the research, was the New History, based in Fernand Braudel, Jacques Le Goff, Marc Bloch and Peter Burke. Authors that served as reference on Comenius are, among others: Olivier Cauly, João Luiz Gasparin, Franco Cambi, Frederick Eby, Jean Piaget, Will Monroe, Sérgio Covello, Latourette and Walker. The conclusion of this philosophical-juridical work pointed to the verification of convergences between Comenius thought and the mentioned Declaration of Jomtien, evidencing notable presence in the concepts construction of right to education, as one of its fundamental columns in contemporaneity. The research was built on an universal ideal, that transcends seasons and find the intrinsically human desire of equality through knowledge and intend to serve as subsidy and motivation for new studies on Comenius thought related to the right to education.